Quality of nutrition services in primary health care facilities: Implications for integrating nutrition into the health system in Bangladesh - Billah, Masum; Saha, Kuntal K.; Khan, Abdullah Nurus Salam; Chowdhury, Ashfaqul Haq; Garnett, Sarah P.; Arifeen, S. E.; Menon, Purnima (Public Library of Science, 2017)
Background In 2011, the Bangladesh Government introduced the National Nutrition Services (NNS) by leveraging the existing health infrastructure to deliver nutrition services to pregnant woman and children. This study examined the quality of nutrition services provided during antenatal care (ANC) and management of sick children younger than five years. Methods Service delivery quality was assessed across three dimensions; structural readiness, process and outcome. Structural readiness was assessed by observing the presence of equipment, guidelines and register/reporting forms in ANC rooms and consulting areas for sick children at 37 primary healthcare facilities in 12 sub-districts. In addition, the training and knowledge relevant to nutrition service delivery of 95 healthcare providers was determined. The process of nutrition service delivery was assessed by observing 381 ANC visits and 826 sick children consultations. Satisfaction with the service was the outcome and was determined by interviewing 541 mothers/caregivers of sick children. Results Structural readiness to provide nutrition services was higher for ANC compared to management of sick children; 73% of ANC rooms had >5 of the 13 essential items while only 13% of the designated areas for management of sick children had >5 of the 13 essential items. One in five (19%) healthcare providers had received nutrition training through the NNS. Delivery of the nutrition services was poor: <30% of women received all four key antenatal nutrition services, 25% of sick children had their weight checked against a growth-chart and <1% had their height measured. Nevertheless, most mothers/caregivers rated their satisfaction of the service above average. Conclusions Strengthening the provision of equipment and increasing the coverage of training are imperative to improve nutrition services. Inherent barriers to implementing nutrition services in primary health care, especially high caseloads during the management of sick under-five children, should be considered to identify alternative and appropriate service delivery platforms before nationwide scale up.